Uniform Mortgage Regulation and Distortion in Capital Allocation. (28th September 2021) - Zhang, Tim
Abstract: The federal mortgage policy, the conforming loan limit (CLL), was spatially uniform before the 2008 crisis, despite remarkable heterogeneity across geography. I show that in areas that experienced a larger decline in the jumbo loan share following an increase in the CLL, lenders raised jumbo loan approval rates, lowered mortgage rates to defend short-term market share, extended credit to riskier borrowers, and incurred deteriorated asset quality in the long run. This result is not explained away by credit supply or demand changes, the bunching effect, or reverse causality. Instead, my evidence is consistent with a competition channel: the effect of CLL increases on jumbo loan credit expansion is significantly exaggerated in a more competitive jumbo-lending market. Overall, my findings suggest that the securitization policies of the government-sponsored enterprises can induce spillovers on the jumbo market segment and influence credit allocation.